The national drug policy 2005 and government's role in monitoring the pharmaceutical market: a critical analysis - Khan, Mohammad Mozammel Hossain (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.